Tunable metasurfaces for visible and SWIR applications - Lee, Chang-Won (Nano Converg, 2020)
Demand on optical or photonic applications in the visible or short-wavelength infrared (SWIR) spectra, such as vision, virtual or augmented displays, imaging, spectroscopy, remote sensing (LIDAR), chemical reaction sensing, microscopy, and photonic integrated circuits, has envisaged new type of subwavelength-featured materials and devices for controlling electromagnetic waves. The study on metasurfaces, of which the thickness is either comparable to or smaller than the wavelength of the considered incoming electromagnetic wave, has been grown rapidly to embrace the needs of developing sub 100-micron active photonic pixelated devices and their arrayed form. Meta-atoms in metasurfaces are now actively controlled under external stimuli to lead to a large phase shift upon the incident light, which has provided a huge potential for arrayed two-dimensional active optics. This short review summarizes actively tunable or reconfigurable metasurfaces for the visible or SWIR spectra, to account for the physical operating principles and the current issues to overcome.